Electric loads of the Ryazan State Radio Engineering University for august – october 2017 - Vasileva T. N., Pushkin V. A., Zhizhnov D. A. (Interactive science, 2018)
in the article the authors considered electric loads for the period of August – October 2017. The values of mathematical expectation, dispersion, standard deviation, coefficient of variation of electrical loads, as well as the maximum and minimum of load values per day, month, quarter are determined.
Keywords: система электроснабжения; power supply system; электрические нагрузки; максимальное и минимальное значения электрических нагрузок; electric loads; maximum and minimum values of electrical loads